Avaliação da atividade antibacteriana e da toxicidade da geoprópolis de Melipona subnitida (Ducke, 1910) e Scaptotrigona depilis (Moure, 1910) - SANTOS, Danilo Costa dos (2023)
The uncontrolled use of antibiotics has led to increased resistance of pathogenic bacteria, which cause various health problems. As a result, there is a need to seek effective, safe and sustainable alternatives for the control and treatment of these multiresistant microorganisms. In this sense, the use of natural products with therapeutic potential has been increasingly studied. Geopropolis is a natural product derived from stingless bees and has been presented as a viable possibility for the synthesis and development of new drugs because it presents a diversity of chemical compounds with biological activities. The present study aimed to evaluate the antibacterial activity, antibiotic modulation and toxicity of geopropolis extracts from two species of stingless bees, Melipona subnitida (Ducke, 1910) and Scaptotrigona depilis (Moure, 1942) against standard and multiresistant bacteria Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. Extract samples were collected in a meliponary located in Camaragibe, Pernambuco, Brazil. The extracts were obtained by maceration technique using ethyl acetate solvent. Assays to determine the Minimum Inhibitory Concentration (MIC) were performed using the broth microdilution method for both bacterial strains. The modulation of the antibiotic action was carried out with the antimicrobials ampicillin, gentamicin and norfloxacin. Toxicity was performed on the in vivo model Drosophila melanogaster. Antibacterial tests showed that both extracts had biological activity against the tested strains. M. subnitida extract showed better inhibitory effects on microbial growth compared to S. depilis extract, with concentrations of 64, 64 and 256 μg/mL against standard strains of S. aureus, E. coli and P. aeruginosa and of 128, 85 and 512 μg/mL against the multidrug resistant ones. Some associations between the extracts and the tested antibiotics resulted in synergistic effects and increased the spectrum of antibacterial action, decreasing the MIC of the drugs. Toxic effects were not observed during in vivo model tests. These results underscore the importance of studies using natural products in alternative therapies, as well as pointing to extracts as potential candidates for the development of new treatments against baterial infections,